1 Corinthians 7:17–24 Identity and human dignity amidst power and liminality - Punt, J. 1962- (2012)
Paul’s concern with identity, and in particular the identity of the believer in relation to Jesus Christ, is an important concern in his writings. In the midst of an important section dedicated to advice and instruction on marriage in his first letter to the Corinthians, Paul encouraged his audience in 1 Corinthians 7:17-24 to remain in the calling by, or position in, which they were called. Concerning these circumstances he refers to circumcision (1 Cor 7:18-19) and slavery (1 Cor 7:21-23) by name. These Pauline instructions are investigated against the backdrop of both the 1st century CE context and post-apartheid South Africa, where issues of identity and marginality rub shoulders with claims to ownership and entitlement, on the one hand, and issues of human dignity, on the other.
Keywords: Ethnicity; Gender; Paul; Post-apartheid South Africa; Sexuality; Slavery